Artificial Intelligence (AI) in the Field of Tahfiz: A Simulation Study of ChatGPT Interaction in Qur’anic Murajaʿah - Abd Muhaimin Ahmad; Muhammad Arif Musa (Centre of Quranic Research (CQR), University of Malaya, 2026)
Indexed by Scopus